Legal Extension Strategies to Increase Awareness of Drinking Water Contaminant Regulatory Framework. (30th December 2021) - Janasie, Catherine; Deans, Olivia; Harris, Taylor
Abstract: It is important for stakeholders, scientists, industry, lawyers, and decision‐makers to understand the varying approaches to regulating drinking water contaminants. To increase awareness and understanding among stakeholder audiences of the legal framework for drinking water protection, the National Sea Grant Law Center (NSGLC) at the University of Mississippi School of Law has developed and implemented research and extension projects for lead, nitrates, and per‐and polyfluorinated substances (PFAS). The NSGLC's mission is to encourage a well‐informed constituency by providing legal information and analysis to the Sea Grant community, policy makers, and the general public through a variety of products and services. For each contaminant, the NSGLC conducted legal research to identify relevant laws, regulations, policies, and court decisions to gain an in‐depth understanding of the existing legal framework. The NSGLC then translated its information on the current legal framework, identified gaps, and potential solutions into a variety of outreach programming. For each of the relevant drinking water contaminants, the NSGLC has taken different outreach approaches. For lead, the NSGLC has worked with an interdisciplinary academic team to conduct community‐based research and outreach directly to families. With nitrates, the NSGLC has focused more on professional development for attorneys, natural resource managers, and other policy makers. With PFAS, the NSGLC is proposing a hybrid approach, drawing on lessons learned from its previous projects and the COVID‐19 pandemic, to disseminate information to both professionals and communities. This case study will synthesize key findings on the legal overview, potential legal issues, and outreach efforts for lead, nitrates, and PFAS.